FLA. CONST. OF 1885, art. I, § 20 - (:unkn) unknown (General Publisher, 1885)
Declared the right of the people to keep and bear arms shall not be infringed, but the legislature shall have the right to regulate the manner in which arms are borne.
--
Keywords: GUARANTEED RIGHT